2016
DOI: 10.1515/jvetres-2016-0012
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the pre- and postpartum body condition scores and periparturient indices and fertility in high-yielding dairy cows

Abstract: Introduction: The aim of this study was to investigate the relationship between body condition score (BCS) determined on the dry-off day, calving day, and in the first month of lactation, its changes during the dry period and early lactation, and periparturient indices and fertility in high-producing dairy cows. Material and Methods: The experiment was conducted in two herds: A and B, located in Western Poland. The studies were conducted on 116 and 108 Polish Holstein-Friesian dairy cows respectively, with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
6
1
Order By: Relevance
“…Our data show that the BCS at the beginning of transitional period (3.5) and at parturition (3.35) were higher than the recommend scores of 3.25 and ≤ 3.0 (Stefańska et al 2016).…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Our data show that the BCS at the beginning of transitional period (3.5) and at parturition (3.35) were higher than the recommend scores of 3.25 and ≤ 3.0 (Stefańska et al 2016).…”
Section: Discussioncontrasting
confidence: 50%
“…Our data show that the BCS at the beginning of transitional period (3.5) and at parturition (3.35) were higher than the recommend scores of 3.25 and ≤ 3.0 (Stefańska et al 2016 ). The animals lost 0.45 points during the first month of lactation, which was higher than recommended by Stefanska et al (2016), who reported that losses should not be > 0.25 during the first month to avoid impairment to the animals’ health.…”
Section: Discussionmentioning
confidence: 45%
“…Dairy cows with a high BCS at the beginning of the transitional period may present a high loss of BCS during the postpartum period, which may cause impaired immune function and an intense proinflammatory state; these factors increase the risk of the cow developing diseases during the postpartum period [25,32,33,36]. Our results evidenced that the lame cows had the BCS at the beginning of the transition period (3.7) above than the recommended (3.25) [36].…”
Section: Discussionmentioning
confidence: 78%
“…On the other hand, after the peak of lactation, the energy needs decreasing, which also is associated with decreasing the milk yield and lactation curve. In this case, if the diets are not well balancing (too high-energy diet level in compiling to the milk production) it might affect improving the BCS in late-lactation dairy cows and then during the dry-off period, which has a negative effect because excessive energy intake prepartum leads to metabolic problems and decreases DMI in the following lactation and loss in milk production [48].…”
Section: Discussionmentioning
confidence: 99%